A APLIKASI SISTEM PARKIR UNIVERSITAS WIDYA DHARMA KLATEN - Hendro Joko Prasetyo; Mariana Windarti; Agustinus Suradi; Istri Sulistyowati (Journal of Computer Science and Technology, 2022)
The parking management information system at Widya Dharma University Klaten is a form of parking information system to collect data and parking arrangements whose application plans will be used at Widya Dharma University Klaten. The purpose of this study is to create a parking system application that can later be used as a parking system aid which is computerized so that it is expected to be more efficient and have efficiency values ​​that can improve service quality and increase income. The research method uses direct observation, while also reading the literature or literature. In this study, namely the implementation of parking management with computerized data collection of vehicle numbers. Research materials and materials include data on parking locations, population of parking vehicles which include cars or motorbikes in the Widya Dharma University area. This design software uses Microsoft Visual Foxpro 9.0 application software, for database design using SQL Server 2000, Microsoft Office 2007 (Word, Excel, Powerpoint, Visio). The results of this study are a computerized Parking System Application which can later be used by Widya University Dharma Klaten so that it is expected to be able to produce information quickly, save time and also for prevention efforts against vehicle theft in the Widya Dharma Klaten University campus. In addition, it can be used to calculate how much rupiah is generated, if there is an activity such as a graduation ceremony, so that the distribution of results can be evenly distributed and there is no mutual suspicion between parking officers (security guards). Keywords: Parking Information System, Microsoft Visual Foxpro 9.0, SQL Server 2000